PENGELOLAAN ZAKAT PRODUKTIF MELALUI PROGRAM SENYUM MANDIRI DALAM PEMBERDAYAAN EKONOMI MUSTAHIQ DI RUMAH ZAKAT CABANG CIREBON - Ridwan, Mohamad; Andalasari, Lilis; Setiani, Reka Indah; Merliana, Rizka (Ecobankers : Journal of Economy and Banking, 2020)
Poverty is a complex problem that is influenced by various interrelated factors. In the principles of Islamic economics, several economic instruments can help social interests, one of them is the use of zakat funds. Zakat is one of the pillars of Islam which is functioned to help the needy, poor, and Dhu'afa by spending part of their assets. Through good zakat management, it is hoped that it can reduce poverty and even make welfare rates evenly distributed. The welfare of Mustahiq is the most important part of the goal of managing zakat. Therefore Rumah Zakat has an empowerment program to increase the economic level of Mustahiq in the form of an independent smile program. This research is descriptive qualitative research that aims to determine the management of productive zakat at Rumah Zakat in the economic empowerment of Mustahiq through the Senyum Mandiri program. Data collection methods used are observation, interviews, documentation, and data triangulation. Based on the research results, it can be concluded that the Senyum Mandiri Program in economic empowerment through productive zakat is very helpful in alleviating poverty, and through this program, the recipients of funds receive business guidance so that they gain skills in entrepreneurship Abstrak Kemiskinan merupakan masalah kompleks yang dipengaruhi oleh berbagai faktor yang saling berkaitan. Dalam prinsip ekonomi Islam terdapat beberapa instrumen ekonomi yang dapat membantu kepentingan sosial salah satunya pemanfaatan dana zakat. Zakat merupakan salah satu rukun islam yang difungsikan untuk menolong orang yang fakir, miskin dan kaum dhu’afa dengan mengeluarkan sebagian harta yang dimiliki. Melalui pengelolaan zakat yang baik, sangat diharapkan dapat mengurangi angka kemiskinan dan bahkan membuat angka kesejahteraan secara merata. Kesejahteraan mustahiq merupakan bagian terpenting dalam tujuan pengelolaan zakat. Oleh karena itu Rumah Zakat memiliki program pemberdayaan untuk meningkatkan taraf ekonomi mustahiq berupa program senyum mandiri. Penelitian ini merupakan penelitian kualitatif deskriptif yang bertujuan untuk mengetahui pengelolaan zakat produktif di Rumah Zakat dalam pemberdayaan ekonomi mustahiq melalui program Senyum Mandiri.Metode pengumpulan data yang digunakan menggunakan observasi, wawancara, dokumentasi dan triangulasi data. Dari hasil penelitian yang dilakukan dapat disimpulkan bahwa Program Senyum Mandiri dalam pemberdayaan ekonomi melalui zakat produktif ini sangat membantu dalam pengentasan kemiskinan dan melalui program ini penerima dana meperoleh bimbingan usaha sehingga mendapatkan skill dalam berwirausaha.